Young, Munson and Okiishi's A brief introduction to fluid mechanics - Young, Donald F.; Okiishi, T. H. (Theodore Hisao), 1939-; Hochstein, John I.; Gerhart, Andrew L.
"A Brief Introduction to Fluid Mechanics, Sixth Edition, is an abridged version of a more comprehensive treatment found in Fundamentals of Fluid Mechanics by Munson, Young, and Okiishi. Although this latter work continues to be received successfully by students and colleagues, it is a large volume containing much more material than can be covered in a typical one-semester undergraduate fluid mechanics course. A consideration of the numerous fluid mechanics texts that have been written during the past several decades reveals that there is a definite trend toward larger and larger books. This trend is understandable because the knowledge base in fluid mechanics has increased, along with the desire to include a broader scope of topics in an undergraduate course. Unfortunately, one of the dangers in this trend is that these large books can become intimidating to students who may have difficulty, in a beginning course, focusing on basic principles without getting lost in peripheral material. It is with this background in mind that the authors felt that a shorter but comprehensive text, covering the basic concepts and principles of fluid mechanics in a modern style, was needed. In this abridged version, there is still more than ample material for a one-semester undergraduate fluid mechanics course. We have made every effort to retain the principal features of the original book while presenting the essential material in a more concise and focused manner that will be helpful to the beginning student. This sixth edition comes with a new look-a standardized format intended to increase accessibility. Concerning the content, the authors strove to continue the distinguished tradition of this text. We have sought to augment it, drawing on our many years of teaching experience. Based on our experience and feedback from colleagues and students, we have made updates to this edition"--